DIGITAL MARKETING BASED ENTREPRENEURSHIP TRAINING TO INCREASE MSMES SALES PERFORMANCE - Muhamad Al Faruq Abdullah; Didin Hikmah Perkasa (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
This community service program aims to enhance the sales performance of Micro, Small, and Medium Enterprises (MSMEs) through digital marketing based entrepreneurship training. MSMEs play a crucial role in local economic development; however, many business owners still face limitations in utilizing digital platforms effectively, resulting in restricted market reach and low sales growth. This program was conducted on Sunday, 26 October 2025, at RPTRA Rambutan, West Jakarta, and involved 20 local women MSME owners from the surrounding community. The implementation employed a structured and participatory approach consisting of entrepreneurship orientation, digital marketing training, hands-on practice, mentoring, and evaluation. The training materials focused on digital branding, social media marketing, content creation, and basic utilization of online marketplaces. The results indicate a significant improvement in participants’ understanding of digital marketing concepts, increased confidence in managing digital promotional channels, and enhanced ability to create simple digital content for business purposes. Participants also demonstrated greater awareness of digital sales opportunities and the strategic role of digital marketing in supporting business sustainability. The findings suggest that digital marketing based entrepreneurship training is an effective community empowerment strategy to strengthen MSME competitiveness and support sustainable business development in the digital era. Continuous mentoring and follow-up programs are recommended to ensure long-term impact and consistent implementation of digital marketing practices among MSMEs.